2002
DOI: 10.1097/00004872-200203000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria in hypertensive patients with electrocardiographic left ventricular hypertrophy: The LIFE Study

Abstract: In patients with moderately severe hypertension, left ventricular hypertrophy on two consecutive ECGs is associated with increased prevalences of micro- and macroalbuminuria compared to patients without persistent ECG left ventricular hypertrophy. High albumin excretion was related to left ventricular hypertrophy independent of age, blood pressure, diabetes, race, serum creatinine or smoking, suggesting parallel cardiac damage and albuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
104
1
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(124 citation statements)
references
References 41 publications
11
104
1
8
Order By: Relevance
“…These patients might also be more prone to regression of cardiovascular changes following BP reduction during antihypertensive treatment. The association between elevated urine albumin excretion and cardiovascular hypertrophy in essential hypertension demonstrated by us 15 and others 23,24,[26][27][28][29] may, therefore, be due not only to higher BP in these patients but also a generalised increased cardiovascular sensibility to BP-induced cardiovascular changes. Therefore, we plan to investigate whether these patients have special genetic polymorphisms within the renin-angiotensin system 33 such as angiotensinconverting enzyme polymorphism (ACE*I/D), angiotensinogen polymorphism (AGT*T/C) and angiotensin II-receptor type 1 polymorphism (AT1R*A/C).…”
Section: Journal Of Human Hypertensionmentioning
confidence: 91%
See 1 more Smart Citation
“…These patients might also be more prone to regression of cardiovascular changes following BP reduction during antihypertensive treatment. The association between elevated urine albumin excretion and cardiovascular hypertrophy in essential hypertension demonstrated by us 15 and others 23,24,[26][27][28][29] may, therefore, be due not only to higher BP in these patients but also a generalised increased cardiovascular sensibility to BP-induced cardiovascular changes. Therefore, we plan to investigate whether these patients have special genetic polymorphisms within the renin-angiotensin system 33 such as angiotensinconverting enzyme polymorphism (ACE*I/D), angiotensinogen polymorphism (AGT*T/C) and angiotensin II-receptor type 1 polymorphism (AT1R*A/C).…”
Section: Journal Of Human Hypertensionmentioning
confidence: 91%
“…4,13,14 In hypertensive patients with LV hypertrophy on electrocardiography (ECG) we recently found that elevated urine albumin excretion assessed as increased urine albumin/creatinine ratio (UACR) and LV mass assessed by ECG were related to high BP suggesting parallel cardiac and glomerular vascular damage. 15 However, LV mass and UACR were at the same time related to each other independently of systolic BP indicating a more direct relationship between cardiac and glomerular vascular damage.…”
Section: Introductionmentioning
confidence: 93%
“…1 Moreover, the association between UAE and increased CVD mortality in high-risk groups begins at levels of UAE below clinically defined thresholds for microalbuminuria. 1 Subclinical CVD, such as left ventricular (LV) hypertrophy [2][3][4][5][6] and increased carotid artery intima-media thickness (IMT), [7][8][9][10][11][12] has been associated with microalbuminuria among individuals at high risk for CVD. Whether the presence of increased UAE provides any additional predictive value for the presence of subclinical CVD in groups not at high risk aside from established, independent CVD risk factors remains unestablished.…”
mentioning
confidence: 99%
“…[10][11][12] In this study, patients with multiple OD (that is, LVH, carotid atherosclerosis and MA) were older, more frequently males, and had higher systolic BP, longer duration of hypertension, greater prevalence of type 2 diabetes, metabolic syndrome and smoking. This underlines the synergic role of several modifiable and non-modifiable risk factors in the development of cardiac and extra-cardiac OD.…”
mentioning
confidence: 67%